Violencia Intrafamiliar durante el confinamiento por la pandemia de SARS COV-19 - Villacrés Beltrán, Daysi (2020)
In the Eugenio Espejo Educational Unit of the city of Babahoyo, a case study was conducted: What are the characteristics of domestic violence during the confinement due to the SARS pandemic COV-19, among 8th grade students of the Eugenio Espejo Educational Unit of the city of Babahoyo? For this reason, we analyzed intra-family violence, we inquired about the intra-family problems that occurred during the confinement in a group of 10 homes, determining the degree of affectation that have been assimilated by the students who have indirectly suffered the ravages of violence in the homes. Interviews were conducted by telephone with 10 students immersed in the intra-family problem, for which a form was prepared with five questions for the collection of information applied to the interviewees, it should be noted that no pressure was ever exerted nor were they forced to answer anything they did not want to answer, Everything was based on a free and voluntary interview, from this it is clear that there are changes in the behavior and low performance of the minors due to the existing intra-family problems caused by economic difficulties due to the confinement by Covid-19, the parents were left without work.